Peran Investasi Terhadap Pertumbuhan Sektor Pertanian Dan Penyerapan Tenaga Kerja Di Provinsi Riau (Jurnal Agribisnis Indonesia, 2025)
The agricultural sector remains the backbone of the economy in Riau Province, but its contribution to employment has been declining in recent years. This raises questions about the effectiveness of government investment and spending in promoting sector growth and creating jobs. This study aims to analyze the effect of investment including foreign investment, domestic investment and government spending on agricultural sector growth and employment in the regencies/cities of Riau Province with a simultaneous equation model approach. This study used panel data for 2018-2023 from 12 districts/cities, and analyzed using the Two Stage Least Square (2SLS) method to estimate the relationship between variables. The results show that domestic investment has a positive and significant effect on agricultural sector growth and employment, while foreign investment shows no significant effect. Government expenditure in the agricultural sector has a negative impact on growth and employment, indicating potential inefficiencies in planning and implementation. Meanwhile, the growth of the agricultural sector is proven to contribute positively to employment. The conclusion of this study confirms that optimization of domestic investment and reformulation of government expenditure allocation are needed to increase agricultural sector output and create more jobs.